1992
DOI: 10.1111/j.1365-2125.1992.tb04127.x
|View full text |Cite
|
Sign up to set email alerts
|

Postmarketing surveillance of captopril for hypertension.

Abstract: 1. A scheme for augmented spontaneous reporting of adverse drug events using advanced view data systems was developed and applied to study 67,698 consecutive patients prescribed captopril in general practice for the treatment of hypertension. 2. Captopril was an effective hypotensive agent in this population, as only 1.9% of patients were withdrawn because of apparent inefficacy. 3. Adverse effects of captopril resulted in withdrawal of treatment in 8.9% of recipients, and such effects were more frequent in el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 9 publications
3
19
1
Order By: Relevance
“…Our hypothesis that the incidence of discontinuation of ACE inhibitors due to cough is much higher in the local population than that reported in other studies (1)(2)(3)7,8) was confirmed in the present study, which showed that approximately 30% of the patients discontinued ACE inhibitors due to cough. In postmarketing studies, the incidence of cough was reported to be as low as 1%.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…Our hypothesis that the incidence of discontinuation of ACE inhibitors due to cough is much higher in the local population than that reported in other studies (1)(2)(3)7,8) was confirmed in the present study, which showed that approximately 30% of the patients discontinued ACE inhibitors due to cough. In postmarketing studies, the incidence of cough was reported to be as low as 1%.…”
Section: Discussioncontrasting
confidence: 56%
“…In postmarketing studies, the incidence of cough was reported to be as low as 1%. (7,8) In the Physicians' Desk Reference, the reported incidence of cough associated with enalapril is 1.3%. (1) In a prospective clinical trial, the incidence of ACE inhibitor-induced cough is reported to be 18.6%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations